DEVELOPMENT OF THE VELOCITY VECTOR INDICATION AT HUD AT LANDING MODE ON THE GROUND-BASED SIMULATOR - K. V. Zakharov; O. I. Tkachenko; A. A. Khokhlov (Научный вестник МГТУ ГА, 2016)
Velocity vector indication at HUD is effective technique for fulfilling carrier landing and landing on short runway. The command glide slope value and carrier velocity are added to traditional algorithm of the velocity vector indication. This make a possibility of carrier landing without using optical landing system (OLS), at heavy deck motion and significant side wind.